Culture of Sciaenops ocellatus L. - Ramos M.A. (Marine aquaculture finfish species diversification, 1995)
Fish culture was started to supply fish in areas where over fishing destroyed the natural stocks like Salmo sp., Onchorhynchus sp. and Alosa alosa (U.S., Canada). The new interest of aquaculture today is the natural resource management and the commercial production of high quality low fat food. In the last 20-30 years, sea bass (Dicentrarchus labrax), sea bream (Sparus aurata) and flat fish (Scophthalmus maximus, Solea sp.) are the principal groups of food fish produced by aquaculturists. The recent intensive culture of yellow tail (Seriola sp.) in Japan, the production of Sceiaenops ocellatus in the U.S. and the fish farming increase in Asia with the production of milk fish (Chanos chanos) are examples of industrial diversification in aquaculture. Sciaenops ocellatus occurs in the coastal area of the Atlantic from New York till the Gulf of Mexico. This is an important species for recreation and competition. Attending the need to produce high quality food, this species has also been used recently for aquaculture purposes and for restocking the sea (Rutledge, 1989; Swingle, 1990). Facilities were built to produce fry for restocking the coastal waters and for intensive and extensive culture of S. ocellatus in Florida and in the Gulf of Mexico.
Seminar of the CIHEAM Network on Technology of Aquaculture in the Mediterranean (TECAM), 1995/06/14-17, Nicosia (Cyprus)